CRISPR-activated patient fibroblasts for modeling of familial Alzheimer's disease. (November 2021) - Inoue, Keiichi
Highlights: Simple fibroblast disease model is useful in neurological research. CRISPR activation of APP and/or BACE1 increases Aβ in fibroblast cultures. CRISPR activation unmasks a g-secretase processivity defect in FAD fibroblast cultures. CRISPR activation provides an additional simple platform to analyze neurological disorders. Abstract: Analyzing an appropriate disease model system is important to conduct disease research. Analyzing cells obtained from patient tissues could not only help elucidate the pathological mechanisms and to develop novel therapy but also lead to personalized medicine in the future. However, it is generally difficult to collect and culture neuronal cells from patients suffering from neurodegenerative disorders. Skin fibroblasts are easier to collect than neurons but may not show the expected pathology when disease-relevant genes are not sufficiently expressed. In this article, I describe an in vitro model system that enables the facile analysis of neurological disease mechanisms in patient fibroblast cultures by CRISPR transcriptional activation of endogenous disease-relevant genes. This system introduces an additional platform to analyze neurodegenerative disorders.